Rancang Bangun Media Pembelajaran Sistem Reproduksi Wanita Berbasis Virtual Reality - Ramadhani, Devy Kurnia; Trisnasari, Dian (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2024)
Midwifery practices have contributed to reducing maternal and child mortality rates by applying biomedical knowledge, one of which is anatomy. Anatomy education typically uses cadavers, models, and books, but it is considered less effective. This study aims to create a virtual reality-based application for quality learning media on the female reproductive system. This research is a development study, which employs a waterfall model to create a high-quality educational media application. The Midwifery Department at Poltekkes Kemenkes Yogyakarta conducted the research in 2022. Based on the needs analysis, it is necessary to develop interactive learning media, one of which utilizes virtual reality technology. Blender for 3D Web applications and A-Frame for Virtual Reality Web. Overall, the application testing resulted in a feasibility percentage of 80.84%. We rated the Virtual Reality application for the Female Reproductive System as very feasible, requiring only minor improvements for learning purposes.